Effect of transport policies to shifting private car users to park-and-ride in Putrajaya, Malaysia - Borhan, Muhamad Nazri; Ismail, Amiruddin; Rahmat, Riza Atiq O.K.; Ambak, Kamarudin (AENSI Publishing Corporation, 2011)
Problems associated with traffic, such as traffic congestion has occurred in Putrajaya due to the increased use of cars. Park-and-Ride (P&R) facility has been introduced to minimize private car into the CBD area. This study is to examine the factors that are influence car users and introducing several new policies (exclusive bus lane and parking charges at worksite parking) to shift to Park and Ride in Putrajaya. The finding were discussed time and cost saving are the important factors to influence car users to use P&R facility. The percentage of car users will shift to P&R was considered high if the bus lane and parking charges are implemented. Introducing exclusive bus lanes will increase the effectiveness (such as punctuality and frequency) of the busses, meanwhile, introducing parking charges will make car user pay more and will increasing their travel cost. To make P&R scheme more successful, introducing exclusive bus lanes and parking charge are the most relevant policy to shift car users to use P&R.